Transformasi Paradigma Kurikulum di Indonesia Dari Kurikulum 1947 Hingga Kurikulum Merdeka: Transformasi Kurikulum sebagai Respon Politik, Ideologis dan Pedagogis - Ayyin Nayyirotul Ummah; M. Sofiyullah Yusuf; Habib Rachman Sayekti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Changes in the Indonesian education curriculum not only represent changes in administrative policy but also reflect a transformation in the educational paradigm influenced by political dynamics, ideology, and pedagogical developments. This article aims to analyze the paradigm shift in Indonesia's national climate from the 1947 Curriculum to the implementation of the Independent Curriculum. This research uses a qualitative descriptive approach through a literature review method, analyzing curriculum documents, educational policies, and various relevant scientific publications. The study results show that every curriculum change is always closely related to the socio-political context and the needs of society at that time, starting from the strengthening of national identity after independence, the centralization of education during the New Order era, to the demands of globalization and technological progress in the reform era. Paradigmatically, there has been a significant shift from a content oriented curriculum to a curriculum based on competency, character, and independent learning. The Merdeka Curriculum is present as the culmination of this transformation by emphasizing learning flexibility, differentiation, and strengthening the Pancasila Student Profile. Thus, curriculum transformation in Indonesia can be understood as a continuous adaptive process in an effort to align national values, student needs, and the challenges of 21st-century global education.